Influence of the Clinical Status on Stress Reticulocytes, CD 36 and CD 49d of SSFA2 Homozygous Sickle Cell Patients Followed in Abidjan - Duni Sawadogo; Aïssata Tolo-Dilkébié; Mahawa Sangaré; Nelly Aguéhoundé; Hermance Kassi; Toussaint Latte (Advances in Hematology)
Background and Objectives. Interactions between sickle cells involving CD 49d, CD36, and the vascular endothelium may initiate vasoocclusion leading to acute painful episodes and multiple organ failure. Materials and Methods. We selected 60 SS patients who had never been treated by hydroxyurea. We performed a total blood count. We identified with immunophenotyping by flow cytometry total reticulocytes their distribution according to the degree of maturity (mature, intermediate, very immature) and CD 36+ and CD 49d+ antigens. Stress reticulocytes corresponded to the sum of intermediate and immature cells. Results. Subjects in crisis had more total reticulocytes and very immature reticulocytes than subjects in stationary phase (P<0.05). During the crisis, total CD 36+ reticulocytes (214 870 ± 107 584/μL versus 148 878 ± 115 024/μL; P<0.05) and the very immature CD 36+ reticulocytes (28.9 ± 7.9% versus 23.0 ± 6.4%; P<0.05) increased. The clinical status had no impact on CD 49d+ reticulocytes. Conclusion. The rates of stress reticulocytes in general and those expressing CD 49d and CD 36 were very high. The clinical status had an influence on CD 36+ reticulocytes. The expression of adhesion molecules is only one of the parameters involved in sickle cell disease crisis.